The radial velocity and metal abundance of the Sextans dwarf spheroidal galaxy. - Da Costa, G. S.; Hatzidimitriou, D.; Irwin, M. J.; McMahon, R. G. (1991)
The AAT FOCAP fibre system has been used to obtain spectra, centred at the Ca II IR-triplet, of 14 stars in the field of the recently discovered Sextans dwarf spheroidal galaxy. Radial velocities derived from these spectra indicate that six of the stars observed are Sextans members. Their velocities cluster closely about a value of 230+/-6 km s^-1^ which we take as the heliocentric velocity of this galaxy. This velocity, when corrected to the galactic rest frame, indicates that Sextans makes a contribution comparable to those of other dSph galaxies, such as Sculptor and Orsa Minor, to calculations of the mass of the galaxy's halo. The spectra of the Sextans members also yield an estimate of the mean abundance of this galaxy: a value of [Fe/H] = - 1.7+/-0.25 dex is suggested from a comparison of the line strengths with those of globular cluster stars. This value is higher than that expected for Sextans from the absolute magnitude-abundance relation, followed by the other galactic dSph galaxies.
Keywords: Abundance; Astrophysics; Dwarf galaxies; Emission Spectra; Galactic Structure; Globular Clusters; Metallicity; Radial Velocity; Spectral Methods; Stellar Motions; Stellar Spectra